Modelling Drivers of Economic Growth in SADC Region - Jeke, Leward; Mauto, Respect Kudzai; Muleya, Henry; Manenge, Robson; Le Roux, Pierre; Abel, Sanderson (International Journal of Economics and Financial Issues, 2026)
The debate on the drivers of economic growth remains inconclusive despite many years’ scholarly research. Countries continue to grapple with the economic growth dilemma experimenting with diverse policies to spur growth in their countries. The objective of the study is to examine the key drivers of economic growth in five African countries; Botswana, Namibia, South Africa, Zambia, and Zimbabwe using panel data from 2010 to 2024. Employing the generalized least squares method with robustness tests via fully modified ordinary least squares, the research findings reveal that macroeconomic variables significantly influence economic growth, with money supply and interest rates having a negative impact, while exchange rates positive influence, with a notable threshold effect. These findings have crucial policy implications, suggesting that policymakers should carefully manage monetary variables, maintain competitive exchange rates, and aim for optimal levels of economic growth drivers to foster sustainable economic development.